2005
DOI: 10.21273/hortsci.40.4.1103d
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anthracnose on Avocado Production in Kenya

Abstract: Avocado is the leading horticultural export in Kenya. In 2003, Kenya exported about 19,000 t, compared to 23 t in 1970. Most of the fruit is exported to the European markets. There are several constraints limiting production of avocado in Kenya, including limited superior varieties or planting material, poor infrastructure, poor market information, and poor tree crop management. Although several diseases infect avocado, the most important are fruit rot pathogens, such as anthracnose, cercospora, and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…whose impact is not widely studied [ 5 , 15 – 18 ]. Wasilwa et al [ 19 ] reported that over 60% of the Kenyan avocado production cannot be marketed because of damage and low quality of fruits associated with anthracnose disease. Despite the huge losses associated with the anthracnose disease of avocado in Kenya, no cultural and molecular studies have been done to identify the causal agent(s).…”
Section: Introductionmentioning
confidence: 99%
“…whose impact is not widely studied [ 5 , 15 – 18 ]. Wasilwa et al [ 19 ] reported that over 60% of the Kenyan avocado production cannot be marketed because of damage and low quality of fruits associated with anthracnose disease. Despite the huge losses associated with the anthracnose disease of avocado in Kenya, no cultural and molecular studies have been done to identify the causal agent(s).…”
Section: Introductionmentioning
confidence: 99%
“…Kenya is one of the major avocado-growing countries in Africa, with an annual production of 186,292 metric tonnes, while Tanzania witnessed a 20% growth in avocado production between 2005 and 2012 [ 1 , 2 , 3 , 4 , 5 , 6 ]. In both countries, avocado fruits are an important source of income and a nutritious food [ 7 , 8 , 9 ] for the smallholder growers and other stakeholders involved in farming and production [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kenya is one of the major avocado-growing countries in Africa, with an annual production of 186,292 metric tonnes, while Tanzania witnessed a 20% growth in avocado production between 2005 and 2012 [ 1 , 2 , 3 , 4 , 5 , 6 ]. In both countries, avocado fruits are an important source of income and a nutritious food [ 7 , 8 , 9 ] for the smallholder growers and other stakeholders involved in farming and production [ 3 , 6 ]. However, avocado fruits are infested by several insect pests, specifically the false codling moth, Thaumatotibia leucotreta Meyrick (Lepidoptera: Tortricidae), and Asian invasive fruit fly, Bactrocera dorsalis (Hendel) (Diptera: Tephritidae), leading to phytosanitary restrictions by importing countries [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the 1970s onwards, however, European buyers began to encourage Kenyan producers to plant different varieties of avocado, such as Fuerte and Haas, to meet European consumer preferences. Approximately 85 per cent of the suppliers of avocado in Kenya are small to medium-scale farmers and farmer groups, the remainder large-scale farmers and Kenyan exporting companies who own their own farms (Wasilwa et al 2006). In terms of revenues, Kenyan avocados are estimated to be split approximately 50:50 between export and domestic markets (interview: government official, 24 November 2014, Nairobi).…”
Section: Commodity Selectionmentioning
confidence: 99%
“…To participate in GVCs, namely to be able to sell to European retailers, Kenyan farmers have switched their type of produce. While local avocado varieties are fibrous, have a soft outer covering and short shelf life (Wasilwa et al 2006), the most common varieties consumed in European markets are Haas and Fuerte, which are smoother, creamier and have longer shelf lives. Thus, local avocado varieties have mostly been replaced with export varieties demanded by European consumers, which had not previously been produced or consumed locally.…”
Section: The Opportunistic Spillover Interaction and Opportunistic Rvcsmentioning
confidence: 99%